Thoraco‐abdominal asymmetry and asynchrony in congenital diaphragmatic hernia. Issue 9 (22nd July 2014) - Laviola, Marianna; Zanini, Andrea; Priori, Rita; Macchini, Francesco; Leva, Ernesto; Torricelli, Maurizio; Ceruti, Clara; Aliverti, Andrea
Abstract Objective Congenital diaphragmatic hernia (CDH) consists of an incomplete formation of the diaphragm and the subsequent herniation of abdominal bowels. Diaphragmatic defect can be repaired by primary closure or placing a patch. Respiratory follow up usually focuses on spirometric and clinical evaluation. The aim of the study was to assess thoraco‐abdominal volumes in CDH patients and to verify whether the action of the diaphragm on the chest wall is altered leading to an asymmetric and asynchronous expansion of the different thoracoabdominal compartments. Patients and Methods Total and compartmental chest wall volumes and asynchronies were measured by Opto‐Electronic Plethysmography in 14 CDH patients (7M/7F, age 5 ± 2 years, 12 left side operated) and in 9 age matched healthy subjects during quiet spontaneous breathing in supine position. Patients were divided in two groups: five patients with suture (group S) and nine patients with diaphragmatic patch (group P). Pulmonary function was assessed by spirometry and spirometric parameters were expressed as Z‐score. Results In group P abdominal contribution to tidal volume was lower than healthy controls and group S. Unlike controls, in both CDH groups the right side of pulmonary rib cage moved inward with a correspondent left side expansion during inspiration. In group S, thoraco‐abdominal asynchronies were higher than in group P and controls, especially in the right side. Five patients belonging to group P had a spirometric obstructive pattern. Conclusions In overall CDH patients a reduced action of the treated (left) hemi‐diaphragm is evident. In patients treated by primary suture, a compensatory action of the right side allows to reach a normal total diaphragmatic displacement and a proper contribution of the whole diaphragm to tidal volume. In patients treated by diaphragmatic patch, instead, thoraco‐abdominal asynchronies are prevented. Pediatr Pulmonol. 2015; 50:915–924. © 2014 Wiley Periodicals, Inc.